Hollywood animal - Eszterhas, Joe; Random House Audio (New York : Random House Audio, 2004)
The screenwriter offers an account of life and fame in the world of the film industry, growing up amid poverty as a Hungarian immigrant, his family life, profiles of Hollywood characters, and his battle with a life-threatening disease
Read by : Eric Bogosian
Keywords: Eszterhas, Joe; Screenwriters -- United States -- Biography; Motion picture industry -- United States; Audiobooks; Hollywood (Los Angeles, Calif.) -- Biography